An extended interpretation of the thermodynamic theory, including an additional energy associated with a decrease in mass. (13th February 2006) - Krasnoholovets, Volodymyr; Tane, Jean-Louis
Although its practical efficiency is unquestionable, the thermodynamic tool presents a slight inconsistency from the theoretical point of view. After exposing arguments which explain this opinion, a suggestion is put forward to solve the problem. It consists of linking the mass-energy relation ±Δmc² to the laws of thermodynamics. This combination results in a clarification of the theory and opens a bridge between thermodynamics and gravitation. It is shown that the submicroscopic consideration, which is based on the cellular concept of the real physical space when the space is treated as the tessellation lattice, indeed strongly supports the idea of a variation in mass in thermodynamic processes.